Peningkatan Kualitas Hasil Belajar Pembelajaran Ipa Materi Interaksi Makhluk Hidup Dengan Lingkungan Melalui Model Discovery Learning Pada Siswa Kelas Vii (Tujuh) Semester Genap Smp Negeri 1 Simpang Teritip Kabupaten Bangka Barat Tahun Pelajaran 2021/202 - Nunung Afrida (Student Research Journal, 2023)
Based on observations made by researchers in science learning in class VII of SMP Negeri 1 Simpang Teritip, there are still many weaknesses in the implementation of science learning. Teachers are less likely to involve students in the learning process, but teachers are more likely to use lectures that only require memory and memorization without developing insight into thinking and problem solving which allows students to learn more actively. The level of mastery of material by students is still low as evidenced by the learning results of 25 students with KKM (Material Completeness Criteria) > 75, there are 13 students or 55.56% of students who got a score below the KKM with a minimum score of 50. Based on the background that has been explained, then the problem formulation is obtained as follows. Can the use of the Discovery Learning model improve science learning outcomes regarding the interaction of living things with the environment for class VII students at SMP Negeri 1 Simpang Teritip? Implementation time for Strengthening Teaching Skills starts from March 28 2022 until 2022. June 5 2022 in the second semester of the 2021/2022 academic year. The results of Cycle 1 learning improvement showed the following results: 16 students got a score of less than 75, 11 students got a score greater than 75, and the student completion rate was 40.74%. In Cycle 2 there were 12 students who got a score less than 75, 15 students got a score greater than 75, and the student completion rate was 55.56%. In cycle 3, 2 students got a score less than 75, 25 students got a score greater than 75, and the student completion rate was 92.59%. The conclusion from writing this PTK is that the application of the recitation method using image media appropriately can improve learning outcomes.